X-Leksia: Creation, Assessment and Implementation - Devaraju, Anusuriya; Techanamurty, Umawathy; Zeratul Izzah, Mohd Yusoh; Mohd Hafiz, Zakaria (INTI International University, 2007)
This paper presents the design and delivery of X-Leksia: a multimedia courseware to aid basic reading skills in Malay language among the pre-school dyslexics. The courseware has been developed based on multi-sensory teaching approach. It supports the visual, auditory, kinaesthetic elements via multimedia and “learn by doing” exercise that will reinforce each other for optimal learning. The courseware has undergone both formative and summative evaluation with dyslexics and subject matter experts from Dyslecia Association of Wilayah Persekutuan, Kuala Lumpur. The evaluation procedure, criteria and results are presented in this paper. As a result of completing the evaluation procedure, the author found that X-Leksia’s approach was well received by the children and teachers alike although there is still room for improvement. The courseware is hoped to contribute a significant idea to the development of technology in Malay language education for pre-school dyslexics in Malaysia.